Women’s Rights Protection Social Movement in the Modern Armenian Society - Gayane Harutyunyan (Banber Erevani Hamalsarani. Sots'iologia, 2023)
Current research article is devoted to the exploration of women’s rights protection movement in modern Armenian society. The exploration of the current situation of the women’s rights protection movement in modern Armenian society includes two components. Firstly, through an analysis of documents (the Soviet state’s first codes of different years), the study examines the evolution of the women's rights protection social movement from the Soviet Union. This investigation illustrates how the Soviet Union’s political system had formed and shaped the women’s movement, which also affected the further development of the movement in modern Armenian society. Secondly, this research paper is based on an analysis of 34 in-depth interviews performed in Yerevan city from 2020-2023, with informants engaged in different types of women’s rights protection activism during the last 20 years in Armenian society. Information gathered from interviews allowed us to split the history of the development of the movement into two time-lapses in modern Armenian society. Triangulation of qualitative document analysis and in-depth interviews, equally contributed to the understanding of the main features of the women’s rights protection social movement as a whole social phenomenon in Armenian modern society. One of the key findings of the research is that despite the existence of diverse groups of women’s rights protection activists and just individuals coping with social system gender inequalities, there is difficulties in establishing social movement in modern Armenian society. The most prevailing definitions of social movements assume non-institutionalized collective actions with a clear set of goals. Instead, what currently exists in modern Armenian society is a form of street activism organized by efforts of different institutionalized organizations, where people engage in sporadic protests to raise awareness about gender issues and gender inequality. The paper also sheds light on social obstacles that prevent the initiative from becoming an institutionalized social movement for women’s rights protection in Armenia. The main social-cultural obstacles can be seen as a combination of factors including the absence of a general feminist agenda, lack of structural strain pushing for mobilization and social conservatism, etc.